POSISI DAN PENCAPAIAN UMBU LANDU PARANGGI DALAM ARENA SASTRA NASIONAL (TINJAUAN SOSIOLOGI SASTRA PIERRE BOURDIEU) - Astika, I Made (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2013)
This research aimed to describe Paranggi’s in the national literary field. Data sets in this research involved texts and propositions of artists, man of letters, or journalists related to Paranggi. The data sets were collected through the use of documentation and interview techniques. Data were analyzed by describing, comparing, associating, sorting or combining them with the Bourdieu’s theories including arena, habitus, capital, strategy, and other concepts discussing cultural production field. In the national literature, Paranggi has occupied objective position as a consecrated and legitimated poet in his field. Such consecration and legitimacy have been based on the principle of specific legitimacy, i.e. recognition provided by a group of other poets that actually serve as his competitors. In other words, the recognition has positioned him in the art edge as an autonomous artist and not positioned based on the principle of dominant and popular legitimacy. Paranggi has been consistently involved in the field of limited production or the so called high level art. In such a competition, he prefers symbolic capitals, prestige involvement, charisma, authority, consecration, or artistic celebration in poetry. Poetry becomes ideology in Paranggi’s life.Keywords: Paranggi, position, and national literary field.